1999
DOI: 10.1002/(sici)1096-9861(19990726)410:2<178::aid-cne2>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Organization of cortical projections to the medullary subnucleus reticularis dorsalis: A retrograde and anterograde tracing study in the rat

Abstract: The distribution and organization of cortical projections to the subnucleus reticularis dorsalis (SRD), the neighboring cuneate nucleus (Cu), and trigeminal nucleus caudalis (Sp5C) were studied in the rat using microinjections of wheat germ agglutinin-apo horseradish peroxidase-gold and Biotin-Dextran. Cortical cells projecting to the caudal medulla were confined to the contralateral layer V with their descending axons crossing the midline at the level of pyramidal decussation. Cortical afferents to Sp5C origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 42 publications
3
23
0
1
Order By: Relevance
“…These projections originate unilaterally from pyramidal cells of layer V of areas within S1, S2, and caudal insula. In accordance with other studies (Wise and Jones, 1977;Desbois et al, 1999), descending axons from S1 and Ins terminate in deep (III-V) and superficial (I-IIo) laminae of Sp5C, respectively, as confirmed by their relationship with 5-HT 1D /calcitonin generelated peptide (CGRP) primary afferents (supplemental Fig. S1 A, available at www.jneurosci.org as supplemental material).…”
Section: Corticotrigeminal Projections To Brainstem Areas Of Trigeminsupporting
confidence: 90%
“…These projections originate unilaterally from pyramidal cells of layer V of areas within S1, S2, and caudal insula. In accordance with other studies (Wise and Jones, 1977;Desbois et al, 1999), descending axons from S1 and Ins terminate in deep (III-V) and superficial (I-IIo) laminae of Sp5C, respectively, as confirmed by their relationship with 5-HT 1D /calcitonin generelated peptide (CGRP) primary afferents (supplemental Fig. S1 A, available at www.jneurosci.org as supplemental material).…”
Section: Corticotrigeminal Projections To Brainstem Areas Of Trigeminsupporting
confidence: 90%
“…The DRt was shown to relay descending pain facilitation from the anterior cingulate cortex (ACC; Zhang et al, 2005). Additionally, the DRt receives dense innervation from cortical areas, namely from the motor (M1 and M2), somatosensory (S1 and S2) and insular cortex (Desbois et al, 1999; Almeida et al, 2002). Our recent work demonstrated that a high percentage of the cortical projections to the DRt were GABAergic (Figure 2) and the release of GABA at the DRt enhanced DRt pain facilitation (Martins et al, 2015a).…”
Section: The Rvm-vlm-drt Triad As a Key Gateway For Top-down Pain Modmentioning
confidence: 99%
“…Theoretical calculations suggest that currents in the range of 0.1-0.5 mA activate a sphere of tissue with a diameter of Ͻ1 mm (Hentall et al, 1984); nevertheless, we cannot exclude that some of the axons in the reticular formation surrounding the PT were also activated. Both the PT and lower brainstem reticular formation projecting neurons are known to populate only layer V of the motor cortex (Jones and Wise, 1977;Groos et al, 1978;Toyoshima and Sakai, 1982;Kuypers, 1984, 1989;Rapisarda et al, 1985;Ghosh et al, 1988;Nudo and Masterton, 1990;Desbois et al, 1999). All neurons that responded antidromically to stimulation applied to electrodes in the PT will be referred to as pyramidal tract neurons (PTNs).…”
Section: Identification Of Neuronsmentioning
confidence: 99%